Reflective practice - Hargreaves, Janet; Page, Louise (Malden, MA : Polity, 2013)
Reflective practice is an essential skill for those working in health and social care, but why is it so vital and how can it be learned? As inter-disciplinary working becomes more common, finding shared ways of reflection on practice are becoming more and more important. This book uses stories and exercises to enable readers to develop their skills. Its emphasis is on the practical, from how to construct a reflective essay to the ethical ambiguities of whistleblowing and constructing a professional persona.
Includes bibliographical references (pages 182-188) and index.
Keywords: Medical care -- Philosophy; Medical care -- Psychological aspects; Social service -- Philosophy; Social service -- Practice; Social service -- Psychological aspects; Reflection (Philosophy); Philosophy, Medical; Health Personnel -- psychology; Professional Practice; Social work